A Novel Gain-of-Function Nav1.9 Mutation in a Child With Episodic Pain - Huang, Jianying; Estacion, Mark; Zhao, Peng; Dib-Hajj, Fadia B.; Schulman, Betsy; Abicht, Angela; Kurth, Ingo; Brockmann, Knut; Waxman, Stephen G.; Dib-Hajj, Sulayman D. (Frontiers in Neuroscience, 2019)
Voltage-gated sodium channel Nav1.9 is a threshold channel that regulates action potential firing. Nav1.9 is preferentially expressed in myenteric neurons, and small-diameter dorsal root ganglion (DRG) and trigeminal ganglion neurons including nociceptors. Recent studies have demonstrated a monogenic Mendelian link of Nav1.9 to human pain disorders. Gain-of-function variants in Nav1.9, which cause smaller depolarizations of RMP, have been identified in patients with familial episodic pain type 3 (FEPS3) and the more common pain disorder small fiber neuropathy. To explore the phenotypic spectrum of Nav1.9 channelopathy, here we report a new Nav1.9 mutation, N816K, in a child with early-onset episodic pain in both legs, episodic abdominal pain, and chronic constipation. Sequencing of further selected pain genes was normal. N816K alters a residue at the N-terminus of loop 2, proximal to the cytoplasmic terminus of transmembrane segment 6 in domain II. Voltage-clamp recordings demonstrate that Nav1.9-N816K significantly increases current density and hyperpolarizes voltage-dependence of activation by 10 mV, enabling a larger window current. Current-clamp recordings in DRG neurons shows that N816K channels depolarize RMP of small DRG neurons by 7 mV, reduce current threshold of firing an action potential and render DRG neurons hyperexcitable. Taken together these data demonstrate gain-of-function attributes of the newly described N816K mutation at the channel and cellular levels, which are consistent with a pain phenotype in the carrier of this mutation.